INDICATION OF CLIMATE HUMIDITY IN CENTRAL ASIA: EVIDENCE FROM THE GRANULOMETRIC RECORD OF BOTTOM SEDIMENTS IN LAKE KHUBSUGUL (MONGOLIA) FOR THE LAST 450 KA - Fedotov A.P.; Ziborova G.A.; Khabuev A.V.; Otinova E.L.; Kugakolov S.A.; Rodyakin S.V. (My University, 2006)
One of the methods used for recording environmental variations in the past is the reconstruction of sedimentation facies conditions based on distribution of the terrigenous component and mineral associations. This kind of work was previously carried out successfully to study bottom sediments in Lake Baikal. The present paper is devoted to the results of grain size analysis of a part of the drill core (KDP-01) taken from bottom sediments accumulated in Lake Khubsugul over the last 450 ka.